Analisis Implementasi Kurikulum Merdeka di SDN 187/I Teratai - Aprilia, Rara Nasywa; Fitriani, Desnita; Sari, Silfiyana; Fitri, Dhella Angelina; Khoirunnisa, Khoirunnisa; Rosmalinda, Desy (LPPM Institut Pendidikan Nusantara Global, 2024)
The independent curriculum is a curriculum that is not meant to replace the previous curriculum but to improve the previous curriculum so that it becomes better. In order to explore and hone students' potential from an early age and focus on developing students' character, knowledge, behavior and competencies. This research is motivated by how the curriculum is implemented Merdeka during its trial period in recent years, with the aim of analyzing how learning with the independent curriculum is implemented and the obstacles experienced by teachers in implementing it. This research uses a descriptive qualitative approach, with data collection methods of observation, documentation and interviews. The results of the research show that the implementation or application of the independent curriculum at SDN 187/1 Teratai has been carried out well. The main obstacles experienced are the readiness of human resources, facilities, and several changes in the Independent Curriculum where curriculum changes require intensive training for teachers to be able to understand and implement the Independent Curriculum well. The school's efforts to overcome this are by preparing human resources, adapting learning tools, and following the rules for implementing the curriculum in stages. Evaluations carried out also show the need for increased understanding and direct training related to the Independent Curriculum.